การพัฒนาตัวบ่งชี้สมรรถนะครูสังคม ในศตวรรษที่ 21 สังกัดสำนักงานเขตพื้นที่การศึกษาประถมศึกษาบึงกาฬ - Chaiyasing, Kosai; Chompuwiset, Patcharin (Journal of Graduate School Sakon Nakhon Rajabhat University, 2023)
This study aimed to 1) develop competency indicators for social studies teachers in the 21st century, and 2) test the consistency of the structural model of those competency indicators. A sampling group, obtained through multi-stage random sampling, consisted of 352 teachers and educational personnel working under Bueng Kan Primary Educational Service Area Office. The research instrument was a five-point rating scale test with the content validity context between 0.80 -1.00, the discriminative power (r) equaling 0.23 to 0.87, and the reliability of 0.92. The data were analyzed by basic statistics and confirmatory factor analysis (CFA). The findings were as follows: 1. The model for measuring the social studies teachers’ competency in the 21st century consisted of seven latent variables, and 21 manifest variables, including classroom management, personalities, social studies learning management, knowledge and skills, communication skills, attitudes toward teaching professions, and curriculum efficiency. 2. The developed model was consistent with the empirical data having Chi-square equaling 9.642, degrees of freedom (df) equaling 8, GFI equaling 0.992, CFI equaling 0.998, RMR equaling 0.004, and RMSEA equaling 0.024. The factor loadings were in the range of 0.548– 0.748, including communication skills with a factor loading of 0.548, followed by personalities with a factor loading of 0.650, attitudes toward teaching professions with a factor loading 0.667, classroom management with a factor loading of 0.683, knowledge and skills with a factor loading of 0.715, curriculum efficiency with a factor loading of 0.748, and social studies learning management with a factor loading of 0.765, respectively.